HEAVY METALS ACCUMULATION IN RIPARIAN VEGETATION IN BAIUT METALLOGENIC AREA, MARAMURES COUNTY (ROMANIA) - POPA, Giana; MIHĂIESCU, Tania Cecilia; ODAGIU, Antonia; MIHĂIESCU, Radu; BALINT, Claudia; OLTEAN, Ion (Studia Universitatis Babeș-Bolyai Chemia, 2019)
The present study was focused on evaluating the manner in which heavy metals originated from natural and anthropic sources (former mining activity in Baiut metallogenic area), in the upper basin of the Lăpuș River, transferred into sediments and accumulated in the riparian vegetation. Total concentrations of Pb, Ni, and Cd, classified as priority hazardous substances in the WFD, were measured in samples of water, sediments and some emergent flora species (Equisetum fluviatile, Myosotonaquaticum, Carexaquatilis, Salix fragilis, Mentha aquatica, Juncus spp.), in 4 selected sections of the Lăpuș River, including a reference section (a pollution free area). The heavy metal concentration in collected samples were determined by atomic adsorption spectrometry. In all the monitored sections the heavy metals concentrations were higher in plants than in sediments or water samples. The highest concentrations were recorded for Pb, then for Ni and lastly for Cd in the genus Carex and Salix in the most contaminated river section. The results of the study show that the ability to accumulate heavy metals differs between species, and affinity for a particular metal depends on its bioavailability.